Fundamental analysis - Krantz, Matt (--For dummies., 2023)
Pick stocks, create a portfolio, and build a nest egg Ever wonder how the pros pick the stocks they invest in? Well, most of them use some form of fundamental analysis, a popular method for assessing securities. In Fundamental Analysis For Dummies, you'll get a crash course in valuating publicly traded companies based on their financial statements, overall health, competitors, markets, and the overall economy. You'll also get easy-to-follow advice on how to protect your investments and diversify your portfolio so you can reduce risk without sacrificing returns. Inside... Learn fundamental analysis basics Discover why fundamental analysis works Get your hands on important data Perform a fundamental analysis Understand financial statements Construct financial ratios Read proxy statements Valuate and price stocks.